Professor Robert A. Mertens - In Memoriam - Śliwiński, A. (Archives of Acoustics, 2006)
Professor Robert A. Mertens a creator of the scientific school of acousto-optics in Belgium passed away at home in Antwerpen on 7-th May 2006, 9 days after his 85-th birthday anniversary.He studied mathematics and theoretical physics at the University of Gent and graduated in 1943 (MSc), completed his PhD in 1949 and his DSc (Habilitation) in 1955. After several research positions at the Belgian Interuniversitary Institute of Nuclear Physics and the Belgian National Foundation he became Professor of Theoretical Mechanics at the Faculties of Sciences and Engineering of the University of Gent in 1963. He retired in 1986. He was a member of the Belgian Royal Academy of Sciences and the president of this Academy for 1992. He was a member of European Acoustics Association, a fellow of the Acoustical Society of America and participated in other numerous international scientific organizations.Professor Mertens' scientific interests focused on physical acoustics (theory of the interaction of the piano string and hammer, theoretical acousto-optics), transport theory and theoretical mechanics (nonlinear mechanics, adiabatic invariants, tops) and in the last few years on quantum mechanics (in relation to the Kapitza-Dirac effect and its analogy with acousto-optical interaction).